Diversification of Grid Blocks’ Morphology in Beijing, China, from the View of Block Formation - Liu, Jiankun (International Planning History Society Proceedings, 2022)
Urban blocks are the highly unchangeable units that make up urban form. Grid blocks have been commonly applied in the continuous top-down planning in Beijing, China, since ancient time. However, the uniform urban planning did not lead to standardized block form, but has morphological diversification appeared. Hence, the research attempts to clarify its dynamic from the initial formation process. It investigates the typological formation process of grid blocks in Beijing form historical maps, and their correspondence with urban development stages. It concludes that the construction of grid blocks covers a long time span without any certain order of boundary defining and subdivision forming. The irregularity and diversity in block morphology result in both conflicts and potential in creating urban diversity in the urban renewal in Beijing city.